Consumption of fertilizers in districts of Slovakia in the period 2006–2015 - Siman, Cyril; Velísková, Yvetta (Acta Agraria Debreceniensis, 2018)
Consumption of fertilizers in districts of Slovakia in the period 2006–2015 Water quality in the surface streams is influenced by several factors. One of important information which can help us to solve problems with quality of water in water body is a distribution of point and non-point pollution sources in a river basin and also amount of pollutants released from them to surface streams. An example of a point source of pollution is the outlet from wastewater treatment plants (industry, urban areas, farms, etc.). On the other hand the most significant non-point source of pollution is considered the application of fertilizers in agriculture. In this paper we have evaluated consumption of organic and industrial fertilizers in Slovakia in the period 2006–2015. Total (in tonnes) and average (in kg ha-1) consumption of industrial and organic fertilizers was analyzed. In monitored period, the amount of applied organic fertilizers was much higher than the amount of applied industrial fertilizers and in addition a significant part of total fertilizers consumption had nitrogenous fertilizers in a group of industrial fertilizers. In a group of industrial fertilizers during the period 2006–2015 we observed just moderately increasing in their consumption, while in the period 2010–2015 the average amount of applied industrial fertilizers per hectare of agricultural land increased by about 20 kg ha-1. On the other hand, in a group of organic fertilizers we observed a decreasing in consumption of fertilizers.